PARTISIPASI DAN KONTRIBUSI TENAGA KERJA WANITA PADA USAHA KERIPIK UBI KAYU TERHADAP PENDAPATAN RUMAH TANGGA DI KELURAHAN KULIM KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Tibrani Tibrani (UIR Press, 2016)
The role of female laborers is not only a housewife but also has multiple roles in her family. This study aims to analyze: (1) Characteristics of female labor and business profile of cassava chips, (2) The amount of female worker participation, (3) The amount of female labor contribution to cassava chips business to household income, 4) Factors influencing the participation of female workers in cassava chips business. This research was conducted in Kulim District Tenayan Raya District from January to May 2016 using survey method. The sample of the study was deliberately taken by 33 female workers. The results showed that the average age of female workers was 33 years old, 9 years old with 3 years of work experience and 4 family dependents. Furthermore, female work participation rate (TPK) on cassava chips business is 1.52% with contribution of female worker earnings to total household income is 33,37%. F-calculation results show that simultaneously the value of adjusted coefficient R square (R2) 75.20%. Partially, the factors that influence significantly to participation are age factor, work experience, and woman worker wage at 90% and 95% confidence level.